The regulation of reporter transgene expression for diverse biological imaging applications - Alexandria S. Battison; Joseph R. Merrill; Jeremy C. Borniger; Scott K. Lyons (npj Imaging)
Abstract A common strategy in biological research is to use the expression of a reporter transgene to non-destructively visualize or measure a biological parameter or process that is otherwise not visible or readily detectable. Genetic reporters have greatly impacted practically all fields of biological research, from visualizing biology in bacteria and microbes, through plant biology, to preclinical research in higher eukaryotes. Fundamentally, many reporter gene assays are reliant upon the expression of a relatively small number of transgenes (e.g., green fluorescent protein (GFP) or firefly luciferase (Fluc)), however, by regulating their expression in different ways, it is possible to generate enormous diversity in the specific aspects of biology measured. For the purposes of this review, rather than focus on the non-invasive imaging modalities or reporter transgenes themselves (recently reviewed1,2), we will instead discuss how reporter transgene expression can be manipulated to generate a huge variety of biological readouts, with specific emphasis in the fields of preclinical oncology and neuroscience, now coming together in the nascent field of cancer neuroscience.